2019
DOI: 10.1111/jfs.12689
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the effect of ethyl pyruvate on the surface contamination of sausage to Listeria monocytogenes by using Q‐PCR assay

Abstract: In this study, we examined the effect of ethyl pyruvate on the efficacy of the inactivation of Listeria monocytogenes on the surface of sausage samples by using quantitative PCR (Q‐PCR). Propidium monoazide (PMA) was used for direct quantification of viable and dead cells. The samples inoculated with L. monocytogenes (~3 to 4 log CFU/mL) and uninoculated samples were treated with 0, 42, 105, and 420 mg/L vaporized ethyl pyruvate (EP) in 1 L volume containers. Sausage samples were tested on Days 0, 7, 14, 21, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Ethyl pyruvate (EP), a simple derivative of pyruvic acid, is widely used as a therapeutic agent (Lee et al, 2017;Cetin et al, 2019) with multi-functional properties including anti-inflammatory, anti-oxidative, anti-apoptotic, and ion-chelating effects (Lee et al, 2017). Currently classified as generally safe by the US Food and Drug Administration, EP is used as a food additive in foods.…”
Section: Introductionmentioning
confidence: 99%
“…Ethyl pyruvate (EP), a simple derivative of pyruvic acid, is widely used as a therapeutic agent (Lee et al, 2017;Cetin et al, 2019) with multi-functional properties including anti-inflammatory, anti-oxidative, anti-apoptotic, and ion-chelating effects (Lee et al, 2017). Currently classified as generally safe by the US Food and Drug Administration, EP is used as a food additive in foods.…”
Section: Introductionmentioning
confidence: 99%
“…According to the evaluation conducted by the United States Food and Drug Administration (FDA), EP has been categorized as being safe for consumption in food products. A research group first reported that vaporized EP could be used to decontaminate green onion and baby spinach (Durak et al, 2012) followed by parsley decontamination by Tornuk and Durak (2015), control of postharvest quality and fungal damage of strawberry and cherry fruits by Bozkurt et al (2016), reduction of Salmonella Enteritidis in raw chicken meat by Çetin et al (2019), inactivation of Listeria monocytogenes on sausage surface by Cetin et al (2019) and recently EP treatment against Escherichia coli O157:H7 and Salmonella Typhimurium on cherry tomatoes by Ucak Ozkaya et al (2021). This study aimed to examine the efficacy of vaporized EP decontamination in reducing the presence of E. coli O157:H7 on lettuce samples.…”
mentioning
confidence: 99%